Combining electrocardiographic criteria for predicting acute total left main coronary artery occlusion - Liu, Chunwei; Yang, Fan; Hu, Yuecheng; Zhang, Jingxia; Li, Ximing; Guo, Zhigang; Liu, Yin; Cong, Hongliang (Frontiers in Cardiovascular Medicine, 2022)
Background Prediction of left main artery (LM) occlusion may contribute to the administration of early reperfusion. We sought to identify electrocardiographic (ECG) features associated with acute total LM occlusion and explore the relationship between ECG features and collateral circulation. Methods We retrospectively studied ECGs in 84 consecutive patients with LM occlusion between January 2001 and April 2022. The ECG findings in these patients were compared with those in 468 consecutive patients with LM subtotal occlusion and non-LM occlusion. Results Three main ECG patterns were described according to the characteristics of ST elevation (STE) in LM occlusion: ST-segment elevation myocardial infarction (STEMI), STE in aVR with diffuse ST depression, and STE in both aVR and aVL. These ECG patterns were associated with different collateral filling territories. One-third STEMI in LM occlusion showed STE in the precordial leads including V1, while 2/3 STEMI showed STE in the precordial leads from V2 to V5 without STE in V1. The following ECG characteristics predicted LM occlusion: STE in both aVR and aVL; STE in I, aVL, and V2–V5 without V1; left anterior fascicular block (LAFB); right bundle branch block (RBBB) + LAFB; and prolongation of the QRS interval. The incidences of STE in aVR and STE in aVR and V1 were higher in LM subtotal occlusion than in LM occlusion. The combination of two different STE criteria (STE in aVR and aVL and STE in I, aVL, V2-V5 without V1) predicted LM occlusion with 62% sensitivity and 95% specificity. The combination of the STE criteria and fascicular block criteria (LAFB and LAFB + RBBB) further improved the specificity to 99% but reduced the sensitivity to 39%. Conclusion The combination of STE criteria predicted LM occlusion with high specificity and moderate sensitivity, and the addition of fascicular block criteria further improved the specificity with some loss of sensitivity.